Comparison of outpatient and home‐based exercise training programmes for COPD: A systematic review and meta‐analysis. Issue 3 (30th November 2017) - Wuytack, Francesca; Devane, Declan; Stovold, Elizabeth; McDonnell, Melissa; Casey, Michelle; McDonnell, Timothy J.; Gillespie, Paddy; Raymakers, Adam; Lacasse, Yves; McCarthy, Bernard
Abstract: Chronic obstructive pulmonary disease is a common, preventable and treatable disease. Exercise training programmes (ETPs) improve symptoms, health‐related quality of life (HRQoL) and exercise capacity, but the optimal setting is unknown. In this review, we compared the effects of ETPs in different settings on HRQoL and exercise capacity. We searched (5 July 2016) the Cochrane Airways Group Specialised Register, ClinicalTrials.gov and World Health Organization trials portal. We selected studies, extracted data and assessed risk of bias with two independent reviewers. We calculated mean differences (MD) with 95% CI. We assessed the quality of evidence using Grades of Recommendation, Assessment, Development and Evaluation. Ten trials (934 participants) were included. Hospital (outpatient) and home‐based ETPs (seven trials) were equally effective at improving HRQoL on the Chronic Respiratory Questionnaire (CRQ) (dyspnoea: MD −0.09, 95% CI: −0.28 to 0.10; fatigue: MD −0.00, 95% CI: −0.18 to 0.17; emotional: MD 0.10, 95% CI: −0.24 to 0.45; and mastery: MD −0.02, 95% CI: −0.28 to 0.25; moderate quality) and on the St George's Respiratory Questionnaire (SGRQ) (MD −0.82, 95% CI: −7.47 to 5.83, low quality). Hospital (outpatient) and community‐based ETPs (three trials) were equally effective at improving HRQoL (CRQ dyspnoea: MD 0.29, 95% CI: −0.05 to 0.62, moderate quality; fatigue: MD −0.02, 95% CI: −1.09 to 1.05, low quality; emotional: MD 0.10, 95% CI: −0.40 to 0.59, moderate quality; and mastery: MD −0.08, 95% CI: −0.45 to 0.28, moderate quality). There was no difference in exercise capacity. There was low to moderate evidence that outpatient and home‐based ETPs are equally effective. See related Editorial Abstract : See related Editorial